COVID-19 Status in Nepal and the Way Forward - Budhathoki, Pravash; Shrestha, Dhan Bahadur; Khadka, Sitaram; Giri, Santoshi (Europasian Journal of Medical Sciences, 2020)
Coronavirus disease (COVID-19) is declared a pandemic on 11 March 2020 due to its global spread. The progression of disease is still at the same speed and the low and middle income countries (LMICs) like Nepal are in a vulnerable state. Starting from the first reported case in January, there have been a total 99 cases as of 7 May 2020 with the chance of further increment in number, but there is no death due to COVID-19 at all in Nepal. The expansion and decentralization of healthcare facilities along with lockdown approach are praiseworthy to contain and treat the disease, however there is still a lack of adequate resources for effective enrichment of healthcare facilities. Poor border security, lack of sufficient health resources, proper health waste management, and social stigmatization remain a major problem for the country. There is not any approved therapy for the treatment of COVID-19, therefore prevention is the best way of effective management in Nepal. The most valid strategy is the application of preventive measures through hand-washing, social distancing, and increasing mass awareness through audio-visual aids about the disease. Simultaneously, the preparedness for effective treatment strategies and application to every healthcare institution handling COVID-19 cases is mandatory.